Pengenalan Literasi Sampah Pada Anak-Anak Melalui Video Dan Permainan - Astuti, Septin Puji; Ristiawan, Ardhi; Ulya, Annida Unnatiq; Purwono, Purwono; Purnasari, Nurwulan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Environmental education creates environmental behaviour of people. Children are social agent who plays prominent role for shaping future life. In order to create environmental consciousness generation environmental education should be delivered to children. This paper reports community engagement activity through providing environmental education for first to third grade of primary school children. The delivery process of environmental education to children was transferred through movies and games. Two movies were played to children have attracted them to understand of the prominent of putting trash to the right litter bin. Meanwhile, game simulation for practicing waste separation resulted 96% of children were able to put rubbish in the right litter: organic, paper and plastic litter. Children who did wrong argue that they made mistakes due to time limit which influenced them to put to the right litter.